Technical report writing today - Pauley, Steven E. (Wadsworth, Cencage Learning, 2014)
Provides thorough coverage of technical writing basics, techniques, and applications. This title offers advanced information on using electronic resumes and documenting electronic sources and Ethics and Globalization sidebars that highlight these two important topics in the technical communication field